Allergen-specific IgA and IgG antibodies as inhibitors of mast cell function in food allergy - Furiness, Kameryn N.; El Ansari, Yasmeen S.; Oettgen, Hans C.; Kanagaratham, Cynthia (Frontiers in Allergy, 2024)
Food allergy, a group of adverse immune responses to normally innocuous food protein antigens, is an increasingly prevalent public health issue. The most common form is IgE-mediated food allergy in which food antigen-induced crosslinking of the high-affinity IgE-receptor, FceRI, on the surface of mast cells triggers the release of inflammatory mediators that contribute to a wide range of clinical manifestations, including systemic anaphylaxis. Mast cells also play a critical function in adaptive immunity to foods, acting as adjuvants for food-antigen driven Th2 cell responses. While the diagnosis and treatment of food allergy has improved in recent years, no curative treatments are currently available. However, there is emerging evidence to suggest that both allergen-specific IgA and IgG antibodies can counter the activating effects of IgE antibodies on mast cells. Most notably, both antigen-specific IgA and IgG antibodies are induced in the course of oral immunotherapy. In this review, we highlight the role of mast cells in food allergy, both as inducers of immediate hypersensitivity reactions and as adjuvants for type 2 adaptive immune responses. Furthermore, we summarize current understanding of the immunomodulatory effects of antigen-specific IgA and IgG antibodies on IgE-induced mast cell activation and effector function. A more comprehensive understanding of the regulatory role of IgA and IgG in food allergy may provide insights into physiologic regulation of immune responses to ingested antigens and could seed novel strategies to treat allergic disease.